2009
DOI: 10.1111/j.1525-1594.2008.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Distribution of Liposome‐Encapsulated Hemoglobin Determined by Positron Emission Tomography

Abstract: Positron emission tomography (PET) is a noninvasive imaging technology that enables the determination of biodistribution of positron emitter-labeled compounds. Lipidic nanoparticles are useful for drug delivery system (DDS), including the artificial oxygen carriers. However, there has been no appropriate method to label preformulated DDS drugs by positron emitters. We have developed a rapid and efficient labeling method for lipid nanoparticles and applied it to determine the movement of liposome-encapsulated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…5a). However, a previous study using MCAO model rats showed that LEH carries oxygen into the other ischemic regions (59). This discrepancy might be due to the differences in the types of models between them.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…5a). However, a previous study using MCAO model rats showed that LEH carries oxygen into the other ischemic regions (59). This discrepancy might be due to the differences in the types of models between them.…”
Section: Discussionmentioning
confidence: 74%
“…LEH elevates the plasma oxygen content in rats (6). However, by using positron emission tomography, an LEH analog was observed in the cerebral cortex but not in the ischemic core of the rats with MCAO caused by PIT (10). Thus, both confirmation that LEH delivers oxygen to the infarction area and determination of the mechanisms that support the protective effects of LEH against brain ischemia are required.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported in the literature suggest the efficacy of Hb liposomes in the treatment of stroke by enhancing the biodistribution of Hb liposomes within the ischemic area in the brain. 144,145,147,[160][161][162][163][164]167,171,191,193,194 In the same way, liposomes for the delivery of angiogenic peptides 140 and VEGF 157 to promote angiogenesis in ischemic tissue were developed, and both formulations effectively promoted vascular regeneration. 140,157 Over the years, many liposomal formulations have been developed for the treatment of stroke.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%
“…72) In the case of LEH having a diameter of 230 nm, it was possible that the liposomes flowed to the vessels beyond the occlusion site, since LEH was small enough to pass through the occlusion. On the other hand, since it is known Size-dependent accumulation of PEG-liposomes in the ischemic region of t-MCAO rats.…”
Section: Liposomal Traffic In the Brainmentioning
confidence: 99%